Analisis Status dan Kelas Kemampuan Kesuburan Tanah pada Beberapa Lahan Tebu di Kecamatan Japah Kabupaten Blora - Siswanto, Dwi; Widjajani, Bakti Wisnu; Siswanto, Siswanto (JURNAL AGROTROPIKA, 2024)
Sugarcane commodity is one of the important commodities in Indonesia. The relationship with the advanced industry of sugarcane is also very close, about 20% in the form of liquid sugar produced from this plant. This study was led to analyze the status and classification of soil fertility capabilities on sugarcane fields in the Japah Area. This study used a survey method with sugarcane fields selected from 9 selected villages and soil sampling depths of 0-20 and 20-40. The fertility status in sugarcane fields in Japah District is included in the Very Low (SR) and Low (R) criteria with C-Organic limiting factors, Potassium reserves, P reserves and low Base Saturation. The fertility ability classification is (T1) Ngiyono K is low, acidic and P is low, (T2) Sumberjo availability K and P are low, acidic, (T3) Wotbakah P is low, (T4) Bogem availability K and P is low, (T5) Gaplokan K and P are low, (T6) Kalinanas K and P are low, (T7) Tlogowungu availability K and low P, (T8) Dologan K and low P, (T9) Ngapus K and low P.Keywords : status, fertility capability, sugarcane land